Chemometric optimization and validation of a novel dispersive liquid liquid microextraction HPLC method for gliclazide, glibenclamide and glimepiride quantitation in serum samples - Monzón, Celina María (2016)
Fil: Monzón, Celina M. Universidad Nacional del Nordeste. Facultad de Ciencias Exactas Naturales y Agrimensura; Argentina.